Etiology, incidence and gender-specific patterns of severe burns in a German Burn Center – Insights of 25 years. Issue 3 (May 2016) - Schiefer, Jennifer Lynn; Perbix, Walter; Grigutsch, Daniel; Zinser, Max; Demir, Erhan; Fuchs, Paul Christian; Schulz, Alexandra
Highlights: Etiology of burns in Germany over 25 years with seasonal distribution. First 25 year evaluation of gender-specific patterns of burns in Germany. Incidence & patents age in regards to etiology of burns. Abstract: Introduction: Burns often require special treatment in specialized burn centers. One of the specialized German burn centers is located in Cologne-Merheim. Only little is known about the etiology of burns in Germany, their monthly distribution and changes over the past 25 years. Methods: We therefore retrospectively analyzed the etiology for all patients treated at the burn intensive care unit (BICU) of Cologne in the last 25 years and categorized them into groups. Thereafter all groups were analyzed according to distribution of age, gender and occurrence. Results: In this way we were able to show that the number of severe burns did not decrease over the time under evaluation and that it did not show seasonal variation. Injured females were older than males but fewer in number. The highest numbers of burns were related to fire, followed by electricity, hot liquids, chemicals and heat contact. Work-related burns occurred mostly with males. However, most of the burns were not work-related for either gender. Conclusion: The number of burns in Germany and in the world is still high, and prevention strategies do not always have the desired effect. This study aims to fill the gap in published burn knowledge in Germany by way of describing the gender differences and etiology characteristics. It can therefore help to identify risks and expand effective burn prevention strategies.